Statistical characteristics of leaked AKR observed at South pole station, Antarctica - Labelle, J.; Schwartz, N. (My University, 2023)
There is mounting evidence of a component of terrestrial auroral kilometric radiation (AKR) that is converted to whistler mode and radiated downward toward the planet, observable even at ground level. Three years of data from South Pole Station in 2018-2020 provide statistics of characteristics of leaked AKR at ground level. The events occur in an approximately 90{day interval around winter solstice, apparently requiring darkness in the ionosphere to be observed at ground level. They favor pre{midnight/midnight magnetic local times, which is consistent with the connection of AKR, observed in space, to auroral substorms. The frequency distribution of ground{level AKR is truncated compared to that observed in space, with primarily the higher end of the frequency range being observed, 400{600 kHz, corresponding to the low altitude range of source heights, 2500-3500 km, assuming generation at the electron cyclotron frequency. Approximately half of the events have maximum radiance exceeding 1.5x10^18 W/m2/Hz, with the strongest events exceeding 10^16 W/m2/Hz; these intensities are up to two orders of magnitude lower than those observed in the ionosphere, suggesting that most of the leaked AKR is at large wave normal angles that cannot penetrate the Earth{ionosphere boundary.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED